The Concept and Characteristics of a Defect of Discretion in Law - Yu. V. Onosov (Сибирское юридическое обозрение, 2023)
The article touches upon the problems associated with defects in law related to discretion. An attempt is made to analyze the approaches of legal scholars to the concepts of “defect of law”, as well as related concepts of “defect of a normative legal act”, “defect of legislation”, “error in law”. Attention is focused on the relationship between the concept of “defect in law” and “quality of law”. In relation to individual branch legal sciences, studies of individual defects have been conducted, however, a unified approach to understanding the essence of the relevant legal phenomenon has not been formed. When analyzing the approaches of various researchers to the essence of the defect in law, it should be noted that the authors point to a violation of the requirements related to the quality of the regulatory legal act. A scientific analysis is carried out of the fact that a law enforcement decision based on various legal defects is associated with discretion. The origins of the concept of “defect in law” are considered, since for the first time it began to be used in industry legal sciences. The point of view on the allocation of an expansive and restrictive understanding of the “defect in law” in scientific circulation is interesting. In the first case, we are talking about the state of legal norms, when the regulation of public relations leads to a violation of the optimal balance of the interests of the state, society and the individual. In the second case, we mean legal regulation, the quality level of which is low, and in this regard, infringement of interests occurs. The article presents the Author's definition of “the defect of discretion in law”, as well as the signs of this concept. The criteria of imperfection, according to the Author, should include gaps in law, conflicts of legal norms, uncertainty of legal regulation, violations of the requirements of legal technology in the construction of texts of normative acts, irrational placement of norms in the legal system, excessive duplication of rules of conduct in acts of different legal force, excessive legal regulation. The signs of the sought concept also include: finding a defect of discretion in the law in a specific substantive element of a legal act, as well as the social harmfulness of the defect affecting discretion in the application of law.